0087 Long-term day-and-night rotating shift work poses a barrier against the normalisation of liver function. (23rd June 2014) - Lin, Yu-Cheng; Hsieh, I-Chun; Chen, Pau-Chung
Abstract : Objectives: To evaluate the impact of day-and-night rotating shift work (RSW) on liver health, we analysed the association between long term RSW exposure and the normalisation of plasma alanine transaminase (ALT) levels over a five-year period. Method: The data from physical examinations, blood tests, abdominal sonographic examinations, personal histories, and occupational records were collected from a cohort of workers in a semiconductor manufacturing company. The sample population was divided into three subgroups for analysis: persistent daytime workers, workers exposed intermittently to RSW (i-RSW), and exposed to persistent RSW (p-RSW). Results: Records were analysed for 1196 male workers with an initial mean age of 32.5 years (SD 6.0 years), of whom 821 were identified as rotating shift workers, including 374 i-RSW and 447 p-RSW workers. At the beginning of the follow-up, 275 were found to have elevated ALT (e-ALT): 25.1% day-time workers, 23.0% i-RSW workers and 21.3% p-RSW workers. Of those with e-ALT at the beginning, 101 workers showed normalised serum ALT levels at the end of five-year follow-up: 10.7% of day-time workers, 8.6% of i-RSW workers, and 6.5% of p-RSW workers; P = 0.016). By performing multivariate logistic regression analyses, and comparing with the persistent daytime co-workers, after controlling for confounding variables, analysis indicated that the workers exposed to p-RSW were 46% less likely (OR, 0.54; 95% CI, 0.30–0.95; P = 0.03) to attain normal ALT levels within a five-year interval. Conclusions: Persistent day-and-night RSW pose a vigorous obstacle to the normalisation of e-ALT among workers with preexing abnormal liver function.